Age-related antibody response to Orthopoxviruses and implications for public health measures: Insights from a South Korean study - Yujin Kim; Green Kim; Gukhui Min; YoungMin Woo; Kyong Ran Peck; Jung Joo Hong; Sun Bean Kim (Elsevier, 2024)
Background: After the eradication of smallpox, there have been no specific public health measures for any Orthopoxviruses (OPXVs). Therefore, it is necessary to countermeasure OPXV infections after Mpox (formerly monkeypox) occurrences, such as the latest global outbreak in 2022-2023. This study aimed to provide crucial insights for the development of effective public health policy making against mpox in populations residing in regions where the virus is not prevalent. Methods: This study used enzyme-linked immunosorbent assays (ELISA) to examine smallpox and mpox antibodies in Koreans with three different age groups. We analyzed 56 sera obtained from a tertiary care hospital in South Korea between September 2022 and April 2023. Plasma levels of antibodies against the viral proteins of smallpox (variola cytokine response-modifying protein B) and MPXV (A29) were measured using enzyme-linked immunosorbent assays. Results: Plasma samples from participants in their early 40 s and older exhibited higher reactivity to viral antigens than those from younger participants. Furthermore, there was a strong positive correlation in antibody positivity for the two different viruses across the sera. Conclusions: The presence of low antibody levels in participants ˂40 years may hinder their ability to defend against OPXV. Therefore, it is imperative to implement effective public health measures to mitigate the transmission of OPXV within the community. These findings serve as fundamental information for devising strategies to combat mpox efficiently, particularly in regions where the virus is not prevalent.